Short-Term Risk of Serious Fall Injuries in Older Adults Initiating and Intensifying Treatment With Antihypertensive Medication. (May 2016) - Shimbo, Daichi; Barrett Bowling, C.; Levitan, Emily B.; Deng, Luqin; Sim, John J.; Huang, Lei; Reynolds, Kristi; Muntner, Paul
Abstract : Background—: Antihypertensive medication use has been associated with an increased risk of falls in some but not all studies. Few data are available on the short-term risk of falls after antihypertensive medication initiation and intensification. Methods and Results—: We examined the association between initiating and intensifying antihypertensive medication and serious fall injuries in a case-crossover study of 90 127 Medicare beneficiaries who were ≥65 years old and had a serious fall injury between July 1, 2007, and December 31, 2012, based on emergency department and inpatient claims. Antihypertensive medication initiation was defined by a prescription fill with no fills in the previous year. Intensification was defined by the addition of a new antihypertensive class, and separately, titration by the addition of a new class or increase in dosage of a current class. Exposures were ascertained for the 15 days before the fall (case period) and six 15-day earlier periods (control periods). Overall, 272, 1508, and 3113 Medicare beneficiaries initiated, added a new class of antihypertensive medication or titrated therapy within 15 days of their serious fall injury. The odds for a serious fall injury was increased during the 15 days after antihypertensive medication initiation (odds ratio, 1.36 [95% confidence interval, 1.19–1.55]), adding a new class (odds ratio, 1.16 [95% confidence interval, 1.10–1.23]), and titration [odds ratio, 1.13 [95% confidence interval, 1.08–1.18]). These associations were attenuated beyond 15 days. Conclusions—: Antihypertensive medication initiation and intensification was associated with a short-term, but not long-term, increased risk of serious fall injuries among older adults. Abstract : Supplemental Digital Content is available in the text.